Health Profile Based on Healthy Family Index, Tambakmas Village From the Results of the PIS-PK Survey - Kirnia Tri Wulandari (Eduvest - Journal of Universal Studies, 2021)
The Healthy Indonesia Program is one of the programs of Nawa Cita's 5th agenda, which is to Improve the Quality of Life of Indonesian People. The purpose of this research is to improve the access of families and their members to comprehensive health services, including promotive and preventive services as well as basic curative and rehabilitative services. The benefits are increasing family access along with their members to comprehensive health services, including promotive and preventive services as well as basic curative and rehabilitative services. Collecting and processing data, including general data and special data, general data is data concerning the working area of Gantrung Health Center, population data and program goals. Special data is data on improving health status, health program coverage, and family and family member data. Identifying health problems and their potential solutions, analyzing and identifying health problems from existing data. At rt levels found some problems on the coverage of low healthy family indicators, this affected the index of healthy families rt levels, the average index of healthy families was on Pre-Healthy.The value is greater if the level of urgency is urgent, or the level of seriousness, or the level of development is increasingly concerning. Then multiply the level of urgency (U) by the level of Seriousness (S) and the level of Development (G). Problem priorities are sorted by multiplication results. Follow-up plans are drawn up jointly between program implementers/efforts with low healthy family indicator achievements. This is the cooperation of health workers and the community in realizing community empowerment in health development. In the follow-up plan still uses the family approach, with the survey data it can be known starting from rw targets, RT, families and individuals